1993
DOI: 10.1126/science.261.5129.1721
|View full text |Cite
|
Sign up to set email alerts
|

Laser 40 Ar/ 39 Ar Evaluation of Slow Cooling and Episodic Loss of 40 Ar from a Sample of Polymetamorphic Muscovite

Abstract: Volume diffusion models predict that crystals with large diffusion dimensions can record a wide range of thermal conditions in the Earth's crust. Direct measurements of the zoning of radiogenic argon-40 in single muscovite porphyroblasts, from a complex terrain in the Vermont Appalachians, record multiple crustal events that span 150 million years. The crystal radius was the effective dimension for argon diffusion (approximately 1000 micrometers). Late deformation features inside the crystals locally decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 16 publications
4
26
0
Order By: Relevance
“…In general, the effective spatial resolution of the laser microprobe is not much smaller than the values for a inferred by Harrison and coworkers from their experiments, so we would not expect laser microprobe mapping of 40 Ar distributions in large mica or hornblende crystals to show any variations related to diffusive loss of radiogenic 40 Ar or uptake of excess 40 Ar. Somewhat surprisingly, such variations have now been documented by numerous studies (e.g., de Jong et al, 1992;Hames and Hodges, 1993;Hames et al, 2008;Hodges and Bowring, 1995;Hodges et al, 1994;Kramar et al, 2001;Onstott et al, 1991;Pickles et al, 1997;Warren et al, 2011). The complex intracrystalline 40 Ar distributions found in the course of these investigations (e.g., Figure 3) indicate how such research may permit better assessment of the physical character of fast-diffusion pathways in natural samples, the impact of polymetamorphism on 40 Ar systematics, and the uptake mechanisms for excess 40 Ar.…”
Section: Laser Microprobe Studiesmentioning
confidence: 88%
See 1 more Smart Citation
“…In general, the effective spatial resolution of the laser microprobe is not much smaller than the values for a inferred by Harrison and coworkers from their experiments, so we would not expect laser microprobe mapping of 40 Ar distributions in large mica or hornblende crystals to show any variations related to diffusive loss of radiogenic 40 Ar or uptake of excess 40 Ar. Somewhat surprisingly, such variations have now been documented by numerous studies (e.g., de Jong et al, 1992;Hames and Hodges, 1993;Hames et al, 2008;Hodges and Bowring, 1995;Hodges et al, 1994;Kramar et al, 2001;Onstott et al, 1991;Pickles et al, 1997;Warren et al, 2011). The complex intracrystalline 40 Ar distributions found in the course of these investigations (e.g., Figure 3) indicate how such research may permit better assessment of the physical character of fast-diffusion pathways in natural samples, the impact of polymetamorphism on 40 Ar systematics, and the uptake mechanisms for excess 40 Ar.…”
Section: Laser Microprobe Studiesmentioning
confidence: 88%
“…First, the bulk diffusion rate should be similar to the rate of diffusion in the intact crystal structure as long as pathways of comparatively retarded or enhanced diffusion are not volumetrically significant. For example, maps of the distribution of argon isotopes in natural crystals display topologies consistent with volume diffusion at the grain scale, with relatively minor modification by fast-diffusion pathways (e.g., Hames and Hodges, 1993;Hodges and Bowring, 1995;Pickles et al, 1997;Reddy et al, 1996;Wartho et al, 1999). Second, the fact that different thermochronometers yield predictable sequences of apparent ages implies that diffusivity, while temperature dependent, is largely an intrinsic property of a mineral.…”
Section: Modes Of Diffusionmentioning
confidence: 93%
“…Protracted and complex age distributions could reflect a history of slow cooling or polymetamorphism in a given source region, or even specific outcrop (c.f. laser single-crystals studies of muscovite in slowly cooled and polymetamorphic rock) [e.g., Hames and Hodges, 1993;Hodges et al, 1994]. Perhaps more commonly in the relatively young and rapidly unroofed settings of the crystalline Himalaya, age distribution with multiple modes is an indication of multiple source regions.…”
Section: Introductionmentioning
confidence: 99%
“…Some (Scaillet et al, 1990;Kelley and Turner, 1991;de Jong et al, 1992;Hames and Hodges, 1993;Hodges et al, 1994;Watson and Cherniak, 2003) found that most of their samples adhered to volume diffusion, resulting in concentration profiles interpretable in terms of simple diffusion through the crystalline lattice. Some studies (Phillips and Onstott, 1988;Onstott et al, 1991;Scaillet et al, 1992;Kelley et al, 1994), however, determined that samples yielded distinct concentration gradients, reflecting a mechanism other than volume diffusion.…”
Section: Background: Fast-path and Multi-diffusionmentioning
confidence: 96%